Sobolev orthogonal polynomials and (M, N)-coherent pairs of measures - Jesus, Márcio (2014)
We introduce the notion of (M, N) −coherent pair of measures as a generalization of the concept of coherent pair of measures introduced by Iserles et al. [A. Iserles, P.E.Koch,S.P.Nørsett,J.M.Sanz-Serna,Onpolynomialsorthogonalwithrespecttocertain Sobolev inner products, J. Approx. Theory 65(2) (1991) 151–175], and subsequently Generalized by several authors. A pair of measures (…)